KUALITAS PERSONAL MENDUKUNG KEMAMPUAN KOMUNIKASI TERAPEUTIK PERAWAT RUMAH SAKIT JIWA - Utami, Budi; Nuryandari; Sutarjo, Puji (Jurnal Media Ilmu Kesehatan, 2013)
Background: : a preliminary study based on inpatient psychiatric hospital Ghrasia Yogyakarta result that 50% of nurses are less open to patients so that less established mutual trust so that the patient seemed closed and silent when asked to communicate and difficult to work with. Good therapeutic communication skills would be possessed by the mental health nurse and the main factors that influence the therapeutic nurse communication skills are personal qualities. Personal qualities are characteristics that must be possessed by a nurse to be able to be therapeutic. Personal qualities include six components: self awareness, values clarification, exploration of feelings, role model, altruism, and ethics and responsibility Research Objectives: This research was conducted in order to determine the quality of personal relationships with communication skills in a therapeutic nurse-patient psychiatric hospital Ghrasia. Methods: a descriptive research with cross sectional correlation. The total sample in this study using a total of 37 people with cluster sampling technique to nurses who work in the maintenance room space Sahadev, Arimbi, Nakula, Shinta and Heroine. Research instruments were questionnaires and observation sheets results were analyzed with Kendall Tau. Results: personal quality nurses in inpatient psychiatric hospitals Ghrasia Yogyakarta is higher by 18 people (48.6%). Communication skills in a therapeutic nurse-patient psychiatric hospital Ghrasia Yoyakarta is good up to 20 people (54.1%). Kendall Tau correlation test results obtained values p (0,038) <0.05. Conslusion: there is a personal relationship with the quality of communication skills in a therapeutic nurse patient psychiatric hospital Ghrasia Yogyakarta. Keywords: Personal qualities, communication skills therapeutic nurse